2007
DOI: 10.1021/je7002786
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of 1-Ethyl-3-methylimidazolium Ethylsulfate and 1-Butyl-3-methylimidazolium Methylsulfate Ionic Liquids

Abstract: Heat capacity, glass-transition, crystallization, and melting temperatures of 1-ethyl-3-methylimidazolium ethylsulfate ([Emim][EtSO 4 ]) and 1-butyl-3-methylimidazolium methylsulfate ([Bmim][MeSO 4 ]) ionic liquids (ILs) have been determined by differential scanning calorimetry (DSC). Their thermal stabilities have been analyzed by thermogravimetric analysis (TGA). Given the effect of the heating rate over the decomposition temperatures, isothermal TGA experiments are proposed as a more appropriate method to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 17 publications
(64 reference statements)
11
113
2
1
Order By: Relevance
“…7 shows that OmimPF 6 started to decompose at 350 • C and it decomposed almost completely at 500 • C, without any char formation. Figure 7 reports DSC results for OmimPF 6 showing two exothermic peaks, which were assigned to PF 6 anion at 370 • C and subsequently imidazolium cation at 400 • C, consistently with previous TGA observations and the difference in molar mass of the counterions (Fernandez et al 2007). Figure 8a shows the TGA curves of the supports after being subjected to oven drying at 105 • C for 2 hours.…”
Section: Figsupporting
confidence: 84%
See 2 more Smart Citations
“…7 shows that OmimPF 6 started to decompose at 350 • C and it decomposed almost completely at 500 • C, without any char formation. Figure 7 reports DSC results for OmimPF 6 showing two exothermic peaks, which were assigned to PF 6 anion at 370 • C and subsequently imidazolium cation at 400 • C, consistently with previous TGA observations and the difference in molar mass of the counterions (Fernandez et al 2007). Figure 8a shows the TGA curves of the supports after being subjected to oven drying at 105 • C for 2 hours.…”
Section: Figsupporting
confidence: 84%
“…Even though the decomposition temperature of pure IL is above the process temperature, the interaction with the support may lead to reduced stability. As a first approach, the thermal stability of pure IL was examined by TGA and DSC within range of 50-600 • C. Previous works showed that common imidazolium-based ILs, such as OmimPF 6 , have very high thermal decomposition temperature and that the anion decomposes before the cation (Fernandez et al 2007). The TGA curve in Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The first range (40-71 • C) corresponds to a dehydration process and can probably be originated from minor water molecules impurity in the sample. Next step of the thermal decomposition in the temperature range (253-320 • C) corresponds to the decomposition of anion [NTf to 400 • C [15][16][17]. In our case, we considered the temperature corresponding to the second degradation step (Td 2 ) as the operational limit for the studied ionic liquid.…”
Section: Thermal Decomposition Studiesmentioning
confidence: 99%
“…The high agreement in the first steps of degradation for the IL mixture evaluated should be completed with a higher collection of this kind of data in order to find a general trend. This aspect would be of interest in order to quickly predict several stability parameters only by knowing pure IL dynamic thermogravimetric analysis (TG) data, which are widely available in the literature [26][27][28][29][30][31][32]. Also other thermal properties of binary mixtures of ILs could be also measured, looking for useful predictive models [33][34][35].…”
Section: Introductionmentioning
confidence: 99%